A multidisciplinary expert opinion on CINV and RINV, unmet needs and practical real-life approaches. Issue 2 (1st February 2020) - Bossi, Paolo; Airoldi, Mario; Aloe Spiriti, Maria Antonietta; Antonuzzo, Andrea; Bonciarelli, Giorgio; Campagna, Alessia; Cassano, Alessandra; Murialdo, Roberto; Musio, Daniela; Silvano, Giovanni
ABSTRACT: Introduction : A range of combination chemotherapy regimens are currently used in clinical practice. However, international antiemetic guidelines often only categorize the emetogenic potential of single agents rather than the emetogenicity of combination chemotherapy regimens. To manage the nausea and vomiting induced by antineoplastic combinations, guidelines suggest antiemetics that are appropriate for the component drug with the highest emetogenic potential. Furthermore, antiemetic guidelines generally do not consider the influence of other factors, including individual patient characteristics, on the emetic effects of cancer treatments. Similarly, the emetogenic potential of radiotherapy is stratified only according to the site of radiation, while other factors contributing to emetic risk are overlooked. Areas covered : An Expert Panel was convened to examine unresolved issues and summarize the current clinical research on managing nausea and vomiting associated with combination chemotherapy and radiotherapy. Expert opinion : The panel identified the incidence of nausea and vomiting induced by multi-drug combination therapies currently used to treat cancer at different anatomic sites and by radiotherapy in the presence of other risk factors. Based on these data and the clinical experience of panel members, several suggestions are made for a practical approach to prevent or manage nausea and vomiting due to chemotherapy regimens and radiation therapy.